Analyzing the Prevalence of Serum Electrolyte Disturbance in Children with Acute Diarrhea and Dehydration - Syed Junet Hussain Shah, Iqra Ali, Amna Tanvir, Qamar U Zaman Shahzad, Ibrahim, Abid Rafiq Chaudhry (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study serum electrolyte derangements among children with acute diarrhea presenting with dehydration. Study Design: Cross-sectional and descriptive study. Place and Duration of Study: This study was conducted at Poonch Medical College, Rawlakot and Shalamar Medical & Dental College, Lahore in the duration from January, 2022 to June, 2022. Methods: There were 132 children with severe acute diarrhea and severe dehydration. The ages of the children ranged from one year to twelve. Children's comprehensive demographic information was gathered after written consent was obtained from parents. We took a blood sample of 5 ml and estimated the serum Sodium and potassium levels. All of the data was analyzed with SPSS 23.0. Results: There were majority male children 82 (62.1%). The Mean age of the cases was 2.2±3.11 years. Frequency of severe dehydration was noted in 52 (38.6%) cases, mild dehydration was in 60 (45.5%) and moderate dehydration in 20 (15.2%) cases. Frequency of hyponatremia and hypokalemia was 85 (64.4%) and 53 (40.2%) children. Conclusion: Our results show that children with acute diarrhea and dehydration have an increased risk of developing hyponatremia and hypokalemia. Significant correlations were found between hyponatremia, hypokalemia, and age, gender, and degrees of dehydration. Keywords: Hypokalemia, Dehydration, Acute Diarrhea, Children